Notes on saying and showing, beauty, and other ideas of interest to art and education, with reference to Ludwig Wittgenstein - Richmond, Stuart (Paideusis, 2008)
Conventionally, it is true an essay has a structure that moves progressively and logically from a beginning to a conclusion. In this group of small essays, I would like to explore my interests in the arts and education by working more with broad strokes, letting meanings emerge from passages in a less linear way, more like a collage, for example. Perhaps such an approach will be congenial for the arts, which are elusive, felt and expressive as much as conceptual.